Membedah Praktik Akuntansi Berdenominasi Mata Uang Asing Perbankan Syariah : Pendekatan Fikih Tematis - Rohim, Abd; sulhani, sulhani; Mughni, Abdul (Jurnal Riset Akuntansi dan Keuangan, 2018)
Abstract. The use ofÂ  rule that origin of muamalah is ibahah (allowed) often causes the practice of sharia banking to be un-creative and not careful about things that are subhat or even haram. Impersonation or modification in addition to the product side also occurs in accounting treatment practices for transactions that occur in Islamic banking. One of them is the treatment of foreign currency denominated transactions that occur in sharia banking. This research uses qualitative method by studying and analyzing fiqih rules on foreign currency denominated transactions that occur in sharia banking. Using the classical fiqh study approach the study concludes that foreign currency-denominated transactions can be grouped into three things: first valuation at the balance sheet date and free of usury, valuation at balance sheet date but prone to usury, and valuation at balance sheet date but not allowed to add assets or corporate earnings. In addition, foreign exchange gains or losses incurred from currency-denominated transactions should take account of the source of the profit / loss first before categorizing it as part of revenues in the sharia bank profit and loss statement.Â Keywords: Foreign curency denominated transactions; Islamic Banking; riba; valuation